An Uncommon Cause of Dysphagia: Postpneumonectomy Syndrome - Rego, Erica; Abdelmeguid, Ahmed; Wang, Yuqi (Kevin); Dewan, Karuna (Case Reports in Otolaryngology, 2021)
Objective. Dysphagia after pneumonectomy is uncommon but concerning. The purpose of this paper is to present a case of dysphonia secondary to postpneumonectomy syndrome. Case Report. A 66-year-old female with stage IIIa adenocarcinoma of the lung was treated with a left pneumonectomy. Three years later, she presented with severe dysphagia, dyspnea, and dysphonia. Esophagram demonstrated severely deviated esophagus to the left of midline, attributed to prior left-sided pneumonectomy, without clear evidence of any external compression. Chest CT scan showed associated leftward mediastinal shift. This patient was treated with voice therapy and an exclusion diet, as the patient elected not to have surgery. Conclusion. This is the first reported case of dysphonia accompanying severe dysphagia following left pneumonectomy. While postpneumonectomy syndrome is rare, a high degree of clinical suspicion is recommended when treating patients with history of pneumonectomy.